Rubberwood: A new source of income for smallholders - Paechana P; Sinthurahat S (IRRDB Symposium on natural rubber(Hevea brasiliensis) V.3: Rubber smallholdings, NR processing and quality and technology Sessions, Vietnam, 14-15 October 1997; p24-31, 1997)
Rubberwood has been extensively and increasingly used over the last two decades in Thailand. The average rubber plantation area which has been felled(ie cut down) is 36,065 ha/annum with an estimated certified total wood yield of 10 million cubic metres. At present, less than 50;of the total amount of rubberwood has been used due to the lack of all-season public roads and unsuitable management programmes for the felling of the rubber trees. The rubberwood price at the farmgate is variable whilst at the factory the rubberwood price is set by weight and does not vary much. It is suggested that the effective use of the increasing value of rubberwood may be one solution to the problem of the falling price of rubber sheet.
Keywords: Rubberwood; Smallholders